Studies of structural and optical variations of nanosized TiO2 introduced by precious metal dopants (Au, Pt, Pd and Ag) - Moloantoa, Ramodike Jacob (University of Limpopo, 2016)
Titania is a cheap and nontoxic polymorphic material of current interest for a variety of technological applications like in gas sensing and photovoltaic cells. Generally, TiO2, with a band gap of 3.2 eV, can only be excited by a small UV fraction of solar light, which accounts for only 3-5% of the solar energy. Various strategies have been pursued including doping with metallic elements (e.g. Fe) or nonmetallic elements (e.g. N) with the aim of shifting the absorption into the visible range. Since the properties and performance of devices, particularly for high-temperature applications, may be affected by the transformation from one phase to another, it is of significant interest to understand the conditions that affect phase transitions. In the present work TiO2 was doped with platinum (Pt), palladium (Pd), silver (Ag) and gold (Au) at doping levels of 5% weight, following the standard sol-gel methods. Structural characterization was carried out using scanning electron microscopy, Raman Spectroscopy and X-ray diffraction. Optical properties were studied using the Diffused reflectance Spectroscopy (DRS). Doping with Pt and Pd resulted in a lower anatase to rutile phase transformation temperature while doping with Au and Ag did not affect the transformation temperature. SEM micrographs show that the surface contains irregular shaped particles which are the aggregation of tiny crystals at lower temperature range, whereas at higher temperatures (900 °C), spheroids are observe.The reflectance spectra of the metal loaded TiO2 reveal substantial strong spectral cut-off starting from roughly 400 nm to the entire visible region (i.e. they show enhanced absorption).
Thesis (M. Sc. (Physics)) -- University of Limpopo, 2016
Keywords: Gas sensing; Photovoltaic cells; Nonetoxic material; Nanostructure material